2016
DOI: 10.3390/ijerph13121254
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Monitoring the Growth of E. coli or HeLa Cells Using an Annular Microelectrode Piezoelectric Biosensor

Abstract: Biological information is obtained from the interaction between the series detection electrode and the organism or the physical field of biological cultures in the non-mass responsive piezoelectric biosensor. Therefore, electric parameter of the electrode will affect the biosensor signal. The electric field distribution of the microelectrode used in this study was simulated using the COMSOL Multiphysics analytical tool. This process showed that the electric field spatial distribution is affected by the width o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Previous investigations have established that P 1 and P 2 are constants spanning several orders of magnitude in actual analyses . Consequently, after connecting 2D PANI electrodes in series into the device (Figure S4b), this device can acutely capture small electrical parameter changes, resulting in pronounced piezoelectric frequency alterations.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous investigations have established that P 1 and P 2 are constants spanning several orders of magnitude in actual analyses . Consequently, after connecting 2D PANI electrodes in series into the device (Figure S4b), this device can acutely capture small electrical parameter changes, resulting in pronounced piezoelectric frequency alterations.…”
Section: Resultsmentioning
confidence: 91%
“…Under the working conditions of PQC, differentiating the above formula yields a new frequency curve model, which reflects that the sensitivity of the PR-SPQC system is jointly determined by C t and Previous investigations have established that P 1 and P 2 are constants spanning several orders of magnitude in actual analyses. 42 Consequently, after connecting 2D PANI electrodes in series into the device (Figure S4b), this device can acutely capture small electrical parameter changes, resulting in pronounced piezoelectric frequency alterations. Due to its affordability and exceptional signal amplification characteristics, these features make SPQC exceptionally well suited for the construction of the PR-SPQC biosensing platform.…”
mentioning
confidence: 99%
“…generated by different electrode structures. Vakilian et al [ 18 ] obtained the optimum size of interdigital electrode for biosensors by COMSOL software to analyze the capacitance value of the sensor influenced by different electrode structural parameters. The simulation results showed that the total capacitance of the electrode with the interdigital length of 100 μm increased by 50% when the interdigital width increased from 10 μm to 25 μm, the capacitance decreased when the interdigital distance fell from 25 μm to 10 μm, and the interdigital thickness had no significant effect on the interfinger capacitance, which proved that the optimum purpose could be attained by adjusting the interdigital width and distance to change the electrode characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, F. Tong et al developed the piezoelectric biosensor with an annular microelectrode as shown in Figure 8. By using micro-scale structure of microelectrode, the optimization in term of current density, rapid response time and mass transfer between the electrodes [62]. The benefit of using piezoresistivity method is that the detection mechanism can be integrated easily into lab-on-a-chip type devices.…”
Section: Piezoelectric Biosensorsmentioning
confidence: 99%